Levodopa-Entacapone-Carbidopa Intestinal Gel in the Treatment of Advanced Parkinson's Disease: A Single Center Real-World Experience - Szabolcs Szatmári; József Attila Szász; Károly Orbán-Kis; Beáta Baróti; Simona Bataga; Marius Ciorba; Előd Ernő Nagy; Radu Mircea Neagoe; István Mihály; Péter Zsombor Szász; Krisztina Kelemen; Attila Frigy; et al. (MDPI AG, 2024)
Levodopa-entacapone-carbidopa intestinal gel infusion is a relatively new treatment option for advanced Parkinson's disease. We aimed to describe and analyze the characteristics of de novo levodopa-entacapone-carbidopa intestinal gel therapy in 20 consecutive patients with advanced Parkinson's disease. We assessed the profile of motor complications by evaluating the following: motor fluctuations, dyskinesias, and the freezing phenomenon at baseline (before the testing period) and before discharge. The treatment significantly reduced the duration of daily hours spent in off time compared with baseline pre-treatment values from a mean of 4.8 ± 0.9 h/day to a mean of 1.4 ± 0.5 h per day (p < 0.001). The duration and severity of peak-dose dyskinesia were also significantly reduced compared with baseline values. Out of the 10 patients who reported freezing, 8 did not present this complication at the pre-discharge assessment. Significant improvements were observed in Hoehn and Yahr scale scores in both the on and off states. The levodopa-entacapone-carbidopa intestinal gel therapy was well tolerated during the follow-up period immediately after initiation. Despite a relatively severe stage of the disease, all patients experienced a significant improvement in motor fluctuations, dyskinesias, and the freezing phenomenon.